Effect of vermicompost and lime on faba bean (Vicia faba L.) grain yield and soil properties on non-responsive acidic soils of Western Amhara, Ethiopia - Beamlaku Alemayehu; Zerfu Bazie; Tadele Amare; Erkihun Alemu; Abere Tenagne; Tarekegn Yibabie; Zelalem Addis; Anteneh Abewa; Abreham Awoke (PLoS ONE, 2025)
Soil acidity is a global problem that limits crop production worldwide. It is the major crop yield-limiting factor in Ethiopia. The experiment was conducted in the Guagusa Shikudad district in western Amhara during the 2021 and 2022 cropping seasons to improve the productivity of faba bean through integrated vermicompost and lime applications. The spacing between rows and plants was 40 and 10 cm, respectively and the gross plot size was 8.4 m². The treatments were zero, half and full lime factorially combined with 0, 5, 10, and 15 t ha ⁻ ¹ vermicompost. Vermicompost and lime were applied separately in rows at planting. The experiment was laid out in a randomized complete block design with three replications. Before planting, a composite surface soil sample at 0–20 cm depth and after harvest from each plot was collected for the determination of soil chemical properties. The soil analysis result indicated that vermicompost and lime significantly increased soil pH and decreased exchangeable acidity. The result also revealed vermicompost and lime significantly (p < 0.001) increased faba bean grain and biomass yield. The maximum faba bean grain yield (2.41 t ha ⁻ ¹) was recorded from the applied 10 t ha ⁻ ¹ vermicompost and full dose of lime (5.6 t ha ⁻ ¹), while the maximum faba bean biomass (5.90 t ha ⁻ ¹) was recorded from the treatment of 15 t ha ⁻ ¹ vermicompost and full dose of lime applied. The minimum grain and biomass yield of faba bean was recorded from the control (vermicompost and lime not applied). Application of 5 t ha ⁻ ¹ vermicompost and a full dose of lime gave an optimum and economical faba bean grain yield. Application of integrated organic and inorganic fertilizers with lime is suggested for the improvement of faba bean grain yield by restoring non-responsive, strongly acidic agricultural soils in the study area and similar agroecology.